STATUS OF THE INTERACTION OF ATER'S TECHNICAL-SCIENTIFIC KNOWLEDGE AND THE TRADITIONAL KNOWLEDGE OF FAMILY FARMERS / Status da interação de conhecimentos técnico-científicos da ATER e o conhecimento tradicional dos agricultores familiares / Situación de la interacción entre los conocimientos técnico-científicos de ATER y los conocimientos tradicionales de los agricultores familiares - Tagliapietra, Odacir Miguel; Carniatto, Irene; Bertolini, Geysler Rogis Flor (REVISTA NERA, 2022)
Resumo: The agricultural modernization, initiated after the Green Revolution, established the agricultural homogenization, helping to transfer technical and scientific knowledge, while neglecting the traditional practices of family farmers. This study aimed to analyze the knowledge interaction between ATER agents and family farmers in order to identify the valorization status of local or traditional knowledge in the practices developed by those farmers. The methods used in the study are characterized as exploratory, qualitative and case study. The research population was formed by family farmers in the municipality of Cascavel/PR, based on data provided by Emater, and 248 family farmers' properties involved in various projects aimed at enhancing local activities were identified. For data collection, 30 families from five different Districts were interviewed. The choice criteria was by convenience. As a result, we identified that the interaction and knowledge sharing between farmers occurs continuously, as farmers usually exchange information about their daily lives and their productive activities in informal conversations and community meetings. The relationship with ATER agents is positive, however it is clear that tacit and explicit knowledge have not been properly socialized. Even though there are economic and knowledge potentialities, commodity crops, which depend on large-scale production, are still predominant and not suitable for family farming. Como citar este artigo: TAGLIAPIETRA, Odacir Miguel; CARNIATTO, Irene; BERTOLINI, Geysler Rogis Flor. Knowledge Interaction between ATER agents and family farmers: status of valuing local or traditional knowledge. Revista NERA, v. 25, n. 62, p. 158-178, jan.-abr., 2022.